Job satisfaction as a predictor of work engagement of banking employees in Windhoek (Journal for Studies in Humanities and Social Sciences, 2018)
Operating in an environment with so many banks offering similar products and services requires banks to have employees that are knowledgeable and have positive job attitudes. Enhancing em-ployees’ levels of job satisfaction will likely influence their levels of work engagement. This study investigated the relation between job satisfaction and work engagement, and which dimensions of job satisfaction best predict work engagement of banking employees in Windhoek, Namibia. The negative job attitudes of bank employees impact on the quality of service delivery and negatively affect customer satisfaction. Having satisfied and engaged employees will most likely improve the quality of service and customer satisfaction within the banking sector. A cross-sectional survey design was used, employing questionnaires to collect data on the biographical details, job satisfaction and work engagement of employees within the banking industry. The sample consisted of employees from two banks, Bank X (n=106) and Bank Y (n=110) in Windhoek. Intrinsic and extrinsic job satisfaction re-ported strong correlations with work engagement. Intrinsic and extrinsic job satisfaction was significant predictors of work engagement, with intrinsic job satisfaction being the stronger predictor. The novelty of this study in Namibia will add to already existing knowledge within Industrial/ Organisational Psychology, and pave the way for future research, and guide the development of interventions to keep bank employees satisfied and engaged in their work, improving on productivity and customer satisfaction. Managers need to assess job satisfaction and employee engagement regularly, identify the factors that impact on employees job attitudes and identify ways to improve job satisfaction, with work engagement having positive impacts on performance and customer satisfaction.